Marine extremes
1 online resource.
Keywords: Marine extremes, as they are conceived of in this volume, encompass environments, activities, events and impacts. Extreme environments found in and around our oceans, including the deep sea and seabed as well as the frozen polar regions, are being seriously affected by both extreme behaviours (dumping and discharge of waste, illegal fishing and piracy) and extreme events (storms, tsunamis, extreme waves and marine heatwaves). The aim of this book is to highlight the multi-disciplinary knowledge and inputs needed to address marine extremes and thereafter to explore opportunities and current challenges. Safe and healthy oceans are important for economic, recreational and cultural activities, in addition to the maintenance of ecosystem services upon which we rely. This volume gathers a unique mix of researchers working on scientific aspects of biological ecosystems and physical processes together with social scientists exploring law and governance options, community preferences, cultural values, economic aspects and criminological drivers and approaches. The multi-disciplinary feature of this book breaks down barriers that arise between disparate fields of research so that integrated solutions to ocean challenges can be found. Overall, this book argues that if we are to achieve sustainable utilisation of our oceans and blue economy goals we must better understand, and respond to, the extreme environments, activities, events and impacts. The book is a valuable addition to the literature and will be of interest to researchers in marine science, ocean governance and natural resource economics, as well as to professionals and government officials concerned with marine policy and planning.